Pengaruh Online Travel Agent terhadap Pemesanan Kamar di Hyatt Regency Yogyakarta - Citra Tartilla Nurdita Putri; Eman Sukmana; I Wayan Lanang Nala; Rinto Dwiatmojo (Samarinda State Polytechnic, 2019)
The development of increasingly sophisticated and rapid technology has made people's lifestyles to change, one of the most striking things is the tendency to do activities in cyberspace, such as purchasing tickets online. Online hotel ticket purchases can be made through the E-Commerce site on the hotel's official website or through third party websites. E-Commerce is known as an Online Travel Agent, with the existence of an Online Travel Agent, prospective guests have a very diverse choice of hotels according to their wants and needs. Prospective guests can directly book hotel rooms and change their bookings easily. The aim of the author is to examine changes in guest behavior, especially guests who previously directly booked a room directly to the hotel, switch to using an Online Travel Agent and find out what promotional strategies hotels should do to increase the number of room bookings through Online Travel Agents. Promotion strategy analysis using SWOT analysis such as SWOT Matrix, IFAS, EFAS, Cartesian Diagram, Internal and External Matrix. The results of the analysis of internal factors and external factors show that the Hyatt Regency Yogyakarta hotel has a strong market competitive position in competition with other five star hotels. This shows that the hotel must continue to make efforts to improve product quality, facilities and services as well as maximize product sales.